2010
DOI: 10.1002/hep.23519
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Activates Deoxynucleotide Synthesis in Nondividing Hepatocytes by Targeting the R2 Gene

Abstract: Hepatitis B virus (HBV) causes liver diseases from acute hepatitis to cirrhosis and liver cancer. Currently, more than 350 million people are chronic HBV carriers, with devastating prognosis. HBV is a small enveloped noncytopathic virus, containing a circular partially double-stranded DNA genome, and exhibits strong tropism for human liver cells. Infected individuals (acute and chronic) secrete about 10 7 to 10 11 virions per day to the bloodstream, with each infected cell releasing 50-300 viruses per day. HBV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 35 publications
6
57
0
Order By: Relevance
“…RNR-dependent dNTP production is crucial for HBV propagation, and its inhibition by hydroxyurea (HU) halts mature HBV virion production [7]. Remarkably, HBV induces RRM2 expression in quiescent cells [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…RNR-dependent dNTP production is crucial for HBV propagation, and its inhibition by hydroxyurea (HU) halts mature HBV virion production [7]. Remarkably, HBV induces RRM2 expression in quiescent cells [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the upregulation of the R2 subunit of ribonucleotide reductase by HBx, and the dependence of HBV replication on upregulation of R2 expression suggest that HBx may cause cell cycle entry in order to increase the availability of dNTPs. Recently, it was shown that HBV can increase the cellular concentration of dNTPs in HepG2.2.15 cells, as compared to HepG2 cells (Cohen et al, 2010). Although these findings are intriguing, this increased pool of dNTPs was not directly linked to HBx and not confirmed in HBV-infected normal hepatocytes.…”
Section: Future Directionsmentioning
confidence: 92%
“…While this effect of HBx on cell cycle progression can probably lead to carcinogenesis and thus become deleterious for the host, it is believed that it might be important for the virus to induce expansion of available deoxynucleoside triphosphate pools within the cells which it needs for replication (Bouchard et al, 2003). Indeed, using HepG2 cells, it was reported that HBx is sufficient for the induction of the R2 subunit of the ribonucleotide reductase (RNR) (Cohen et al, 2010). RNR is the key enzyme responsible for de novo dNTP synthesis and is composed of R1 and R2 subunits (Nordlund & Reichard, 2006).…”
Section: Hbx Influences Many Cellular Processesmentioning
confidence: 99%
“…While the R1 subunit is expressed in quiescent cells, the R2 subunit expression is silenced (Chabes et al, 2003). As a consequence of induction of R2 by HBx, the dNTP pool for effective viral production was increased without affecting cell cycle progression (Cohen et al, 2010). Different groups using different models showed that HBx may localize and interact with the proteasome components thereby influencing proteasome subunit composition (Chen et al, 2001;Fischer et al, 1995;Hu et al, 1999;Zhang et al, 2000).…”
Section: Hbx Influences Many Cellular Processesmentioning
confidence: 99%